2012
DOI: 10.1051/0004-6361/201219025
|View full text |Cite
|
Sign up to set email alerts
|

Supernova remnants and candidates detected in theXMM-NewtonM 31 large survey

Abstract: Context. We present the analysis of supernova remnants (SNRs) and candidates in M 31 identified in the XMM-Newton large programme survey of M 31. Supernova remnants are among the brightest X-ray sources in a galaxy. They are good indicators of the recent star-formation activities of galaxies and the interstellar environment in which they evolve. Aims. By combining the X-ray data of sources in M 31 with optical data as well as optical and radio catalogues, we aim to compile a complete, revised list of SNRs emit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 64 publications
1
54
0
Order By: Relevance
“…Note that the effect of the foreground absorption should be very minor, since N H MW values are very similar in the directions of M31, M33, and the LMC (5−7 × 10 21 cm −2 ). 26 objects were confirmed SNRs in Sasaki et al (2012), and another 20 were candidate SNRs. Long et al (2010) present a large catalogue of 82 confirmed SNRs in M33, based on the Chandra ACIS survey of M33 (ChASeM33, Tüllmann et al 2011).…”
Section: X-ray Luminosity Function Of Snrs In the Local Groupmentioning
confidence: 93%
“…Note that the effect of the foreground absorption should be very minor, since N H MW values are very similar in the directions of M31, M33, and the LMC (5−7 × 10 21 cm −2 ). 26 objects were confirmed SNRs in Sasaki et al (2012), and another 20 were candidate SNRs. Long et al (2010) present a large catalogue of 82 confirmed SNRs in M33, based on the Chandra ACIS survey of M33 (ChASeM33, Tüllmann et al 2011).…”
Section: X-ray Luminosity Function Of Snrs In the Local Groupmentioning
confidence: 93%
“…They clearly stand out in our cube, and we have detected one more (labeled SNR2). We have used the same criteria as Lee & Lee (2014), based on Braun & Walterbos et al (2011), in the X-ray and optical wavelengths can be found in Sasaki et al (2012). figure 24).…”
Section: Supernova Remnantsmentioning
confidence: 99%
“…Because the detection was optimised to find point sources, we also removed known supernova remnants (SNRs included in Sasaki et al 2012) from the catalogue when the source was split into multiple spurious detections, because of the extent of the SNR. We discuss these separately in Sect.…”
Section: Catalogue Compilationmentioning
confidence: 99%
“…Most of these SSSs have been found to be associated with optical novae (Pietsch et al 2005aOrio 2006). Another class of X-ray sources are supernova remnants (SNR), which can be spatially resolved in M 31 using X-ray, optical, or radio observations (Kong et al 2002a;Sasaki et al 2012, and references therein).…”
Section: Introductionmentioning
confidence: 99%